A 7-month-old girl with a suspected air embolism complication during a living-donor liver transplantation procedure: a case report - Huang, Dan; Yang, Liqun; Yu, Weifeng; Qi, Bo (Frontiers in Pediatrics, 2023)
Background Pediatric liver transplantation is an important modality for treating biliary atresia. The overall survival rate of pediatric liver transplantation has significantly improved. The incidence of perioperative cardiac events was evaluated, and risk factors were also investigated in adult patients undergoing liver transplantation in previous studies. To the best of our knowledge, this is the first case of a cardiac event during pediatric living donor liver transplantation. Case Summary Our report describes the management of cardiac events during liver transplantation in a 7-month-old girl. ST-segment began to increase to 3.0 mm immediately after reperfusion, with peak ST-segment elevation reaching 13.2 mm after 45min. The procedure ended uneventfully after continuous symptomatic and etiological treatment. It was considered to be the occurrence of an acute air embolism complication of the procedure based on the electrocardiograph and biomarkers. An echocardiogram during follow-up showed a patent foramen ovale with a left-to-right shunt tract width of 2.7 mm. Discussion Pediatric liver transplantation has become a state-of-the-art treatment for children with end-stage liver disease and can improve the quality of life to some extent. These children may be complicated with congenital heart disease, which increases the risk of surgery. Application of echocardiogram, close monitoring, and appropriate management may reduce the incidence of perioperative cardiac events.